HYDROCHEMICAL AND GASEOUS ANOMALIES ON SULFIDE TAILINGS (SALAIR, KEMEROVO REGION) - Svetlana B. Bortnikova; Nataliya V. Yurkevich; Aleksey V. Edelev; Olga P. Saeva; Sofiya P. Grakhova; Sergey S. Volynkin; Yuriy G. Karin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
The relevance of the research consists in obtaining data on the processes occurring in the sulfide mine waste, their transformation under the influence of oxidative factors, migration of toxic components into the environment. The main aim of the research isto determine the vertical zoning by elemental composition and content of gases (carbon disulfide and dimethyl sulfide) in the tailings, as well as to establish thehydrochemical anomalies in the nearest river as a result of migration of potentially toxic elements with water flows from the tailings. Object of the research is the abandoned tailings dump of the Salair mining and processing plant – TalmovskiePeski (Salair, Kemerovo region), containing wastes of cyanidation and flotation of barite-polymetallic ores. Methods. In the field, thermometry, gas analysis, electric exploration by the resistance method in the electrotomography mode were carried out. Solid and liquid sampling was carried out in accordance with generally accepted techniques. The laboratory study of the chemical composition was carried out by the methods of conductometry, potentiometry, capillary electrophoresis, and mass spectrometry with inductively coupled plasma. Results.The vertical distribution of the total element concentrations is determined by the heterogeneity of the stored tailings material. Using the example of two cross sections to a depth of 1,2 m, it was determined that the humidity of the substance increases with depth, and the temperature, pH pastes and aqueous extracts decrease. With depth, the amount of water-soluble species of metals increases due to the transformation of sulfides in acidic conditions, as well as due to the inflow from the upper horizons. The gas generation of carbon disulfide and dimethyl sulfide increases towards the upper layers of the tailings, which is due to the both transformation of minerals, and active functioning of biota in the upper heated layers with a neutral reaction of the medium. As a result of active tailings-water-gas interactions, contrasting hydrochemical anomalies with high metal concentrations are formed in the Malaya Talmovaya River, in the channel of which the tailing dump is located.